The Reality of Field Training Programs for Students of Media and Communication Departments in Saudi Universities: The Department of Media and Communication at King Khalid University as a Model. A Descriptive Study on a Sample of Trainers in Training Entities in Governmental and Private Sectors in the Asir Region, Saudi Arabia" - Al-Qahtani, Dr. Ali bin Abdullah Al-Zuhair (Thi Qar Arts Journal, 2024)
This study aims to identify the reality of training for students of media and communication departments in the Kingdom of Saudi Arabia by studying the reality of training programs for students of the media and communication department at King Khalid University. From the point of view of those responsible for training in government and private sector institutions in the Asir region; In order to determine the suitability of training programs for department students; In terms of content, training methods, and program evaluation tools for trainees’ performance, the study relied on the survey method through a deliberate sample with (40) individuals, males and females, from the study population, which includes workers in public relations departments, newspapers, radio, and television in training agencies in the Asir region. The  study  concluded  that: these  institutions concerned with preparing training programs that respond to the real needs  of  the students, also they combine theoretical information  and practical  applications in the field in  accordance  with the  abilities, skills and knowledge level of students, and  supplement  their  deficiency  through  their  educational  programs in public relations, advertising, journalism,  electronic editing, radio and  television  which adds new art and skills that benefit them in their future. The study revealed that; these training institutions use most of the (11) methods of presenting the training course, including:   lectures, discussions, seminars, conferences, case studies, workshops, role-plays, field training, on-site training, in addition to multimedia. Also, the study explains that these institutions used (5) tools to evaluate the performance of the trainees; including: (the attendance, participating, adherence to instructions, integration with work team, and measuring knowledge and skill through   assignments   and   tasks).